Five Questions to Help Prompt End-of-Life Planning in Neuromuscular Disease - Lipanot, Benjamin J.; Bosslet, Gabriel (Seminars in Respiratory and Critical Care Medicine, 2024)
Patients with neuromuscular disease are living longer lives but continue to have significant and often unpredictable morbidity and mortality. End-of-life planning for these patients is thus an essential part of their medical care. This planning should include the following topics: health care surrogates, swallowing and nutrition, daytime respiratory support, and all aspects of when end of life is near. Adult-onset and early-onset diseases may require different approaches to these topics. All patients with neuromuscular disease will benefit from these discussions to best reach patient-centered goals. We present health care providers these five questions and explanations as a guide.
Keywords: neuromuscular; end of life; goals; planning; surrogates; conversation